2008
DOI: 10.1007/s10571-008-9279-9
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Reactive Oxygen Species and Activation of Akt Signaling Pathway in Neuropathic Pain

Abstract: Neuropathic pain occurs as a result of peripheral or central nervous system injury. Its pathophysiology involves mainly a central sensitization mechanism that may be correlated to many molecules acting in regions involved in pain processing, such as the spinal cord. It has been demonstrated that reactive oxygen species (ROS) and signaling molecules, such as the serine/threonine protein kinase Akt, are involved in neuropathic pain mechanisms. Thus, the aim of this study was to provide evidence of this relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 41 publications
2
30
1
Order By: Relevance
“…Numerous studies have demonstrated activation of AKT in DRG and spinal cord neurons following peripheral nerve injury or inflammation (26,58,59,60,71). In the present study, neither AKT nor pAKT was observed in the suburothelial nerve plexus of control or CYP-treated bladder whole mounts.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Numerous studies have demonstrated activation of AKT in DRG and spinal cord neurons following peripheral nerve injury or inflammation (26,58,59,60,71). In the present study, neither AKT nor pAKT was observed in the suburothelial nerve plexus of control or CYP-treated bladder whole mounts.…”
Section: Discussioncontrasting
confidence: 78%
“…More recently, studies have demonstrated novel roles for AKT signaling in altered sensory/pain processing. For example, basal AKT phosphorylation is present in rodent lumbosacral dorsal root ganglia (DRG) (58,59) and superficial laminae of the spinal cord (26,60) and significantly increases following peripheral nerve injury or inflammation (26,58,59,60,71). Additionally, colocalization of pAKT with markers of unmyelinated, pain-transducing C-fibers such as IB4, TrkA, calcitonin gene-related peptide (CGRP), and transient potential vanilloid-1 channel (TRPV1) (58,59,71,74) has been demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that ROS activates various transcription factors in cultured VSMCs and may function as a signaling molecule in various pathways leading to MAPK, NF-κB, and AP-1 activation. 42,[44][45][46][47][48] . Furthermore, ROS has been implicated to enhance the transcription by activation of NF-κB and AP-1, leading to increased adhesion molecule expression.…”
Section: Discussionmentioning
confidence: 99%
“…First, normobaric hyperoxia treatment has been found to inhibit gp91(phox) expression, Akt activation, NADPH oxidase activity and MMP-2/9 induction; [25][26][27] while Akt activation, NADPH oxidase activity and MMP-2/9 induction have been proven to have important roles in the formation and development of neuropathic pain. [28][29][30][31] Second, InHO can increase the expression of tumor necrosis factor-α converting enzyme, which can convert the transmembrane tumor necrosis factor-α into soluble tumor necrosis factor-α. 21 Transmembrane tumor necrosis factor-α increases hypersensitivity of phenotype of sensory neurons and activate microglia.…”
Section: Discussionmentioning
confidence: 99%